A novel risk score for predicting left atrial and left atrial appendage thrombogenic milieu in patients with non-valvular atrial fibrillation. Issue 192 (August 2020) - Fu, Yuan; Li, Kuibao; Gao, Yuanfeng; Wang, Lefeng; Chen, Mulei; Yang, Xinchun
Abstract: Background: Although the CHADS2 and CHA2DS2-VASc scoring systems are commonly used as measures of thromboembolic risk in patients with nonvalvular atrial fibrillation (NVAF), data are inconsistent as to their value in predicting the presence of left atrial (LA) and/or left atrial appendage (LAA) thrombogenic milieu (TM). The present study aimed to establish a novel risk score to assess the risk of LA and/or LAATM in NVAF patients. Methods: This is a retrospective case-control study that included 125 consecutive patients with NVAF plus TM, as evidenced by transesophageal echocardiography (TEE) during a period from1 January 2010 to 1 February 2017. The controls were 1098 NVAF patients without TM during the same period. Risk factors for LA and/or LAATM were identified using univariable analysis and multivariable logistic regression. The risk score model was developed based on 10-fold validation and multiple regression. Risk model performance was evaluated using receiver operating characteristic (ROC) curves. Net reclassification improvement (NRI) was used for the comparison of C-statistics. The AUCs were compared using the Z test. Results: Among all 1223 NVAF patients, 125 (10.22%) patients had LA and/or LAATM. A score system (0−12) was developed based on the following 6 independent variables identified by 10-fold validation with sequential methods. Different points were assigned for each variable, according to multivariable regression using relative coefficients (coefficient of the index risk factor divided by the lowest coefficient among the 6 risk factors; rounded to closest integer): 1 for blood type A and N-terminal B-type natriuretic peptide (NT-proBNP) ≥864.85 pg/mL; 2 for LAD ≥43.5 mm and age ≥ 73.5 years old; 3 for previous heart failure and previous stroke or TIA. The present risk score system had a sensitivity of 58.3%, specificity of 91.4 and accuracy of 81.6%. The area under the ROC curve (AUC) was 0.832, (95% CI: 0.784–0.881; P < 0.001). The negative predictive value (NPV) was 92% when we set the cut-off point at 4; when the cut-off point was set at 8, the positive predictive value (PPV) was 85.7%. Compared with CHADS2 and CHA2DS2-VASc score, the present novel risk score has better predictive power [net reclassification improvement (NRI) +96.3% and +66.2%, respectively; all P < 0.001]. Conclusion: This study developed a novel risk score to help predicting LA and/or LAATM in NVAF patients, which had higher accuracy than CHADS2 and CHA2DS2-VASc score system. Highlights: ABO blood groups are known to be associated with thromboembolic diseases. Blood type A, NT-proBNP, LAD, age, previous heart failure, previous stroke or TIA were independently associated with TM in NVAF patients. A novel risk score (0-12) was established to evaluate TM risk in NVAF patients.